Pengaruh Media Edukasi Terhadap Pengetahuan dan Sikap Higiene Sanitasi Makanan Jajanan - Azzahro, Siti Muthi'ah; Kurniasari, Ratih (Universitas Airlangga, 2024)
Background: Hygiene and sanitation are health efforts by improving hygiene and health through early maintenance of individuals and their surroundings. Health problems can be contaminated through food and the surrounding environment, one of which is snacks which are currently being traded a lot. Objectives: The purpose of this study was to determine the effect of introspective media, animation media, media games on students' knowledge and attitudes about food hygiene and sanitation at SMPN 5 Karawang Barat. Methods: This study used a quasi-experimental approach with a pre-test and post-test design using a total sampling technique with a sample of 69 respondents. Statistical analysis was performed using the Wilcoxon signed-rank test Results: The results showed that there were significant results between knowledge and attitudes with infographic media, 3D media, and game media with a significant p-value of 0,000. Conclusions: There is an influence of infographic media, 3-dimensional media, game media on students' knowledge and attitudes regarding hygiene, sanitation of snack foods at SMPN 5 Karawang Barat schools.